“Propuesta de un Sistema de Tratamiento de Aguas Residuales Contaminadas con Cromo Total del Proceso de Curtido de la Empresa Curtiembre Rodríguez E.I.R.L - Pompa Castillo, Elvis Tito (2023)
The present investigation seeks to determine the technical and economic viability of the proposal for treatment of wastewater with chrome from the tanning stage of the company Curtiembre Rodríguez EIRL. For this, the following technical studies were carried out to determine the best technologies that allow recirculating and treating the effluent under an approach of saving production costs in consumables. The technical analysis determined that the good practice of direct chrome recirculation allows the recovery of the residual bath from the tanning stage, being usable in 5 production batches. The sixth discharge of residual tanning water would be the only one to be treated by chemical precipitation, technically considering the operating conditions of pH at 8.6 regulated with the alkali NaOH to obtain chromium results below 1.55 mg/l Cr+3, subsequently The residual clarified can be treated with activated carbon with efficiencies greater than 45%, in such a way that the treated water, under this approach, will increase the useful life of the carbon, as well as reduce the cost of consumables. The economic analysis, an economic VAN of S/. 262 465, economic IRR of 105.53%, with a B/C analysis of 1.71 and a payback period of 1.22 years. Therefore, under the correct choice of wastewater treatment system, the company Curtiembre Rodríguez EIRL concludes that the project is technically and economically viable